Distribution of the Galβ1-4Gal epitope among birds: species-specific loss of the glycan structure in chicken and its relatives. - Noriko Suzuki (Public Library of Science (PLoS), 2013)
The Galβ1-4Gal epitope is rarely found in mammals, and the natural antibody against Galβ1-4Gal is rich in human. In contrast, we have previously demonstrated the presence of Galβ1-4Gal in pigeon and ostrich, and the absence of this epitope in chicken. Here, to further investigate the expression of this glycan among birds, egg white glycoproteins and egg yolk IgG from nine species of birds, namely, chicken, duck, emu, guineafowl, ostrich, peafowl, pigeon, quail, and turkey, were analyzed by western blot using an anti-(Galβ1-4Gal) antibody. The results indicated that some egg white glycoproteins from emu, ostrich, and quail, and heavy chains of IgG from all of the birds, except chicken and quail, were stained with the antibody. The presence of Galβ1-4Gal on N-glycans of IgGs from guineafowl, peafowl, and turkey were confirmed by mass spectrometry (MS), MS/MS, and MS(n) analyses. In quail, the presence of Galβ1-4Gal was confirmed by detecting the activities of UDP-galactose: β-galactoside β1,4-galactosyltransferase (β4GalT(Gal)) in various tissues, and by detecting Galβ1-4Gal by western blotting. In contrast, bamboo partridge, which is a close relative of chicken, did not show any detectable activities of β4GalT(Gal) or Galβ1-4Gal on glycoproteins. Because quail, peafowl, turkey, chicken, and bamboo partridge belong to the same family, i.e., Phasianidae, expression of Galβ1-4Gal was most likely differentiated within this family. Considering that Galβ1-4Gal is also expressed in ostrich, emu, and pigeon, which are phylogenetically distant relatives within modern birds, Galβ1-4Gal expression appears to be widely distributed among birds, but might have been abolished in the ancestors of chicken and bamboo partridge.